Originally Posted by

**I Congruent** Ok this is what i got can u tell me if im right?

If we suppose that (S,$\displaystyle \bullet$) is assiociative and let x,y,z$\displaystyle \in$T. Since f is isomorphic f is onto, so there are a,b,c such that f(a)=x, f(b)=y, f(c)=z

x*(y*z)=f(a $\displaystyle \bullet$ (b$\displaystyle \bullet$ c)) since S is a homomorphsim.

= f((a $\displaystyle \bullet$ b) $\displaystyle \bullet$ c) since f is commutative.

=f(a $\displaystyle \bullet$ b) * f(c) since it is a homomorphism

=(f(a)*f(b))*f(c)

=(x*y)*z